Effects of creatine supplementation on endurance cycling combined with short, high-intensity bouts - Godly, A.; Yates, J. W. (Medicine & Science in Sports & Exercise, 1997)
Well-trained cyclists (N = 25) consumed 24 gm of glucose (placebo) or 20 gm of creatine for five days. An incremental simulated 25 km race was performed. It featured six 15-second high-effort bursts evenly spread throughout the task. Creatine supplementation did not have an appreciable effect on endurance cycling performance when combined with short, high-intensity bouts in trained cyclists. Implication. Creatine supplementation does not assist endurance performance.